Energetics and Kinetics of S-State Transitions Monitored by Delayed Chlorophyll Fluorescence - Zaharieva, Ivelina; Dau, Holger (Frontiers in Plant Science, 2019)
Understanding energetic and kinetic parameters of intermediates formed in the course of the reaction cycle (S-state cycle) of photosynthetic water oxidation is of high interest and could support the rationale designs of artificial systems for solar fuels. We use time-resolved measurements of the delayed chlorophyll fluorescence to estimate rate constants, activation energies, free energy differences, and to discriminate between the enthalpic and the entropic contributions to the decrease of the Gibbs free energy of the individual transitions. Using a joint-fit simulation approach, kinetic parameters are determined for the reaction intermediates in the S-state transitions in buffers with different pH in H2O and in D2O.